2000
DOI: 10.1111/j.1728-4465.2000.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of DHS Maternal Mortality Indicators

Abstract: This study presents an assessment of the quality of data relating to maternal mortality collected in 14 Demographic and Health Surveys (DHS) for 13 countries that included a complete sibling history. Four aspects of data quality are considered: completeness of the data for reported events, evidence of omission in the reporting of events, plausibility of the pattern of sibling deaths, and sampling errors of the maternal mortality estimates. Although the data relating to reported events are complete for most var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 6 publications
1
70
1
1
Order By: Relevance
“…Although data sources such as the Demographic and Health Surveys have improved our knowledge of process indicators related to maternal mortality, such as institutional deliveries or skilled attendant at delivery, the estimates of maternal mortality have been disappointing. 29,30 Census data may also provide a unique opportunity to study regional or socioeconomic differentials in maternal mortality, an advantage not offered by estimates from sibling-based methods such as those used by the Demographic and Health Surveys. It is clear, however, that additional validation of this method (for example, in demographic surveillance sites) could lead to increased accuracy of …”
Section: Resultsmentioning
confidence: 99%
“…Although data sources such as the Demographic and Health Surveys have improved our knowledge of process indicators related to maternal mortality, such as institutional deliveries or skilled attendant at delivery, the estimates of maternal mortality have been disappointing. 29,30 Census data may also provide a unique opportunity to study regional or socioeconomic differentials in maternal mortality, an advantage not offered by estimates from sibling-based methods such as those used by the Demographic and Health Surveys. It is clear, however, that additional validation of this method (for example, in demographic surveillance sites) could lead to increased accuracy of …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the sisterhood method underestimates the actual level of maternal mortality. 4,5 Large sample sizes are needed for estimating maternal mortality in this way and the confidence intervals of the estimates are relatively wide. However, the data allow comparisons across countries because of the standard instruments and design.…”
Section: Global Trends In Maternal Mortalitymentioning
confidence: 99%
“…In Nigeria, proportional maternal mortality (PM) was 31.2% and 15.6% in 1990 and 2013 respectively (32). This depicts that death from pregnancy and child birth may be the most important killer of women in the reproductive age group in Nigeria.…”
Section: Current Maternal Mortality Profilementioning
confidence: 99%